2023
DOI: 10.1039/d2tb02797f
|View full text |Cite
|
Sign up to set email alerts
|

Construction of tea tree oil/salicylic acid/palygorskite hybrids for advanced antibacterial and anti-inflammatory performance

Abstract: This study describes the construction of a tailor-made clay-based hybrid with advanced dermocompatibility, antibacterial and anti-inflammatory performances by incorporating tunable ratios of tea tree oil (TTO) and salicylic acid (SA)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Mohammed In a general way, the antibacterial activity of the NE is dependent on its composition, and experimental strains. It has been reported that BB, TTO, and glycyrrhizic acid have an excellent bacteriostatic effect on S. aureus [12,16,55]. Yang et al [12] proved that BB can destroy the permeability of the cell membrane, and inhibit the synthesis of bacterial nucleic acid and protein against S. aureus.…”
Section: Antibacterial Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Mohammed In a general way, the antibacterial activity of the NE is dependent on its composition, and experimental strains. It has been reported that BB, TTO, and glycyrrhizic acid have an excellent bacteriostatic effect on S. aureus [12,16,55]. Yang et al [12] proved that BB can destroy the permeability of the cell membrane, and inhibit the synthesis of bacterial nucleic acid and protein against S. aureus.…”
Section: Antibacterial Evaluationmentioning
confidence: 99%
“…Tea tree oil (TTO) is a colorless-to-light-yellow oily liquid with an aromatic smell, extracted from the fresh leaves of the tea tree; it is rich in a variety of biological active substances, such as terpenes [15]. Because of its broad spectrum of antibacterial [16], anti-inflammatory, and other biological activities [17], it has been widely used in medicine, food, and other industries. However, plant EOs have some disadvantages, such as a poor water solubility and easy decomposition [18], which limit their further application.…”
Section: Introductionmentioning
confidence: 99%